The Suicide of Jackson Maine in A Star Is Born - Synthia Santoso (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
In the thesis, I am interested to see the reasons for Jackson Maine, a famous and successful rock star to end his life based on the film A Star Is Born. To do that, I use Thomas Joiner’s Interpersonal Theory of Suicide. Joiner’s theory discusses the qualities and conditions in his life that may cause him to commit suicide. To see the reasons for Jackson Maine’s death as portrayed in the film, I also use David Brodwell and Kristin Thompson’s Mise-en-Scène theory. Using the approach, I can find the reasons behind his death by analyzing the film’s visual arrangement within the scenes. In my research, I find that Jackson Maine experiences great difficulties and disappointment that he fails to cope and encourages him to end his life. Social disconnections, burdensomeness beliefs, and suicide capabilities become the reasons behind his self-destruction decision. Keywords: Suicide, Mise-en-Scène, Film Analysis, Social Disconnections, Self-destruction.